INFLUENCE OF WEED MANAGEMENT PRACTICES ON CROP GROWTH, NUTRIENT UPTAKE AND YIELD OF GROUNDNUT UNDER IRRIGATION CONDITION - BASAVARAJ KUMBAR; T. V. RAMACHANDRA PRASAD; M. T. SANJAY; G. B. MALLIKARJUNA; VEERESH HATTI; V. MADHUKUMAR (The Bioscan, 2014)
An agronomic investigation was conducted at Main Research Station, Hebbal, Bengaluru during Kharif 2011, with eight treatments [fluazifop-p-butyl 13.4 EC at 100, 134 and 167 g a.i./ha, imazethapyr 10 SL at 100 g a.i./ ha,quizalofop-p-ethyl 5 EC at 50 g a.i./ha , pendimethalin 30 EC at 750 g a.i./ha, hand weeding and unweeded control] were replicated four times in RCBD.All herbicide treatments and hand weeding recorded the significantly higher growth parameters, yield attributesand nutrient uptake in groundnut as compared to unweeded control, whereas, unweeded control lowered the nutrient uptake of groundnut by 44% as compared to hand weeding.Fluazifop-p-butyl 167 g ai/ha @ 20 DAS gave higher pod yield (1681 kg/ha) similar to that of hand weeding (1655 kg/ha) and was on par with imazethapyr 100 g ai/ha @ 20 DAS (1577 kg/ha), Fluazifop-p-butyl 134 g ai/ha (1542 kg/ha) @ 20 DAS, pendimethalin 750 g ai/ha @ 3 DAS (1528 kg/ha) and quizalofop-p-ethyl 50 g ai/ha (1485 kg/ha) due to lower weed competition. Unweeded control lowered the pod yield by 56% (720 kg/ ha) as compared to hand weeding. Thus, adoption of suitable weed management through hand weeding or use of herbicides improved the yield and growth components.